Mycobacteria Protocols - Parish, Tanya; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1998)
In Mycobacteria Protocols, laboratory experts present cutting-edge molecular biology techniques for studying the mycobacteria, a medically significant group of organisms responsible for both human and animal disease-including tuberculosis and leprosy. The methods range from basic culture techniques, cell fractionation, and nucleic acid purification to more advanced protocols for the introduction of cloned DNA into mycobacteria, the use of reporter genes, and the expression of foreign genes. There are also important techniques for mycobacteriophages, genome analysis, chemical and transposon mutagenesis, gene replacement, and analysis of gene expression, as well as such clinically useful techniques as antibiotic susceptibility testing, speciation, and RFLP analysis. Mycobacteria Protocols contains a unique collection of both established and recently developed techniques that have been optimized and adapted for use with mycobacteria. Offering an eminently practical introduction for all those carrying out basic or applied research in this important class of bacteria, Mycobacteria Protocols is certain to become the new standard reference in the field, one from which even expert researchers will learn many time-saving techniques.
Mycobacteria -- Mycobacteria -- Isolation of Genomic DNA from Mycobacteria -- Nucleic-Acid Extraction: Plasmid/Cosmid DNA -- Pulsed Field Gel Electrophoresis for Mycobacteria -- Extraction of RNA from Mycobacteria -- Preparation of Cell-Free Extracts from Mycobacteria -- Preparation of Cell-Wall Fractions from Mycobacteria -- Using MycDB on the World-Wide Web -- Conjugating DNA into Mycobacteria -- Electroporation of Mycobacteria -- Mycobacteriophages -- Chemical Mutagenesis of Mycobacteria -- Tn611 Transposon Mutagenesis in Mycobacterium smegmatis Using a Temperature-Sensitive Delivery System -- Homologous Recombination in Mycobacterium smegmatis -- Gene Replacement in Mycobacterium smegmatis Using a Dominant Negative Selectable Marker -- Gene Replacement in Mycobacterium intracellulare -- Gene Replacement in Mycobacterium bovis BCG -- The Application of Bacterial Luciferase as a Reporter Gene in Mycobacteria -- Green Fluorescent Protein -- Expression of Genes in Mycobacteria -- Secretion of Mammalian Proteins from Mycobacteria -- Intracellular Gene Expression -- 24 Analysis of Mycobacterial Differential Gene Expression by RAP-PCR -- Mycobacterial Speciation -- Species Identification of Mycobacteria Using rDNA Sequencing -- Detection of Mycobacterium tuberculosis by a Calorimetric Polymerase Chain Reaction -- Rapid Detection and Simultaneous Strain Differentiation of Mycobacterium tuberculosis Complex Bacteria by Spoligotyping -- Computer Analysis of IS6110 RFLP Patterns of Mycobacterium tuberculosis -- Detection of Mutations in Mycobacteria by PCR-SSCP (Single-Strand Conformation Polymorphism) -- The Use of Luciferase-Reporter Phage for Antibiotic-Susceptibility Testing of Mycobacteria.
Keywords: Microbiology; Microbiology